The Hypothalamic-Pituitary-Adrenal Axis: What can it Tell us About Stressors? - Armario, Antonio (CNS & Neurological Disorders - Drug Targets, 2006)
The hypothalamic-pituitary-adrenal (HPA) axis is an extremely sensitive physiological system whose activation, with the consequent release of ACTH and glucocorticoids, is triggered by a wide range of psychological experiences and physiological perturbations (stressors). The HPA axis is also activated by a high number of pharmacological agents that markedly differ in structure and function, although the precise mechanisms remain in most cases unknown. Activation of the HPA axis is the consequence of the convergence of stimulatory inputs from different brain regions into the paraventricular nucleus of the hypothalamus (PVN), where the most important ACTH secretagogues (corticotrophin releasing factor, CRF, and arginin-vasopressin, AVP) are formed. Plasma levels of ACTH and corticosterone (the latter under more restricted conditions), are considered as good markers of stress for three main reasons: (a) their plasma levels are proportional to the intensity of emotional and systemic stressors, (b) daily repeated exposure to a stressor usually resulted in reduced ACTH response to the same stressor, that is termed adaptation or habituation; and (c) chronic exposure to stressful situations results in tonic changes in the HPA axis that can be used as indices of the accumulative impact of these situations. These changes can be evaluated under resting conditions (i.e. adrenal weight, CRF and AVP gene expression in the PVN) or after some challenges (administration of CRF, ACTH or dexamethasone) that are classical endocrinological tests. There is also evidence that the activation of the HPA axis may also reflect subtle changes in the characteristics of the stressful situations (unpredictability, lack of control, omission of expected rewards, presence of conspecifics), although this is a topic that requires further studies.
Keywords: adaptation